Spatial Organization of Chromatin: Transcriptional Control of Adaptive Immune Cell Development - Pongubala, Jagan M. R.; Murre, Cornelis (Frontiers in Immunology, 2021)
Higher-order spatial organization of the genome into chromatin compartments (permissive and repressive), self-associating domains (TADs), and regulatory loops provide structural integrity and offer diverse gene regulatory controls. In particular, the chromatin regulatory loops, which bring enhancer and associated transcription factors in close spatial proximity to target gene promoters, play essential roles in regulating gene targets and non-protein-coding regulatory elements. The establishment and maintenance of such chromatin loops are predominantly mediated through key architectural factors including CTCF and the cohesin machinery. In recent years, significant progress has been made in revealing how loops are assembled and how they modulate patterns of gene expression. Here we will discuss the mechanistic principles that underpin the establishment of three-dimensional (3D) chromatin structure and how changes in chromatin topology relate to alterations in gene programs that establish immune cell fate.